2022
DOI: 10.1177/10596011221104295
|View full text |Cite
|
Sign up to set email alerts
|

Leader Trait Self-control and Follower Trust in High-Reliability Contexts: The Mediating Role of Met Expectations in Firefighting

Abstract: Drawing from the theory of met expectations, this study aims to create new knowledge on the antecedents of follower trust in leaders in the context of high-reliability organizations. We hypothesize that highly self-controlled leaders instill more trust than leaders with less self-control, as the former tend to meet follower expectations. This work combines data from a field survey ( N = 256) and a multi-wave field study ( N = 106), using samples of professional firefighters to support our hypotheses that met f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 159 publications
0
2
0
Order By: Relevance
“…Additionally, self-control strengthens the link between leaders’ good moral character and ethical leadership behavior (Sosik et al, 2019). High self-control leaders are also more likely to meet the expectations their followers have about leaders (Rosing et al, 2022). Since our work demonstrates that people prefer to give power to those who exhibit self-control, further understanding of how leader self-control influences followers and team performance is especially important.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, self-control strengthens the link between leaders’ good moral character and ethical leadership behavior (Sosik et al, 2019). High self-control leaders are also more likely to meet the expectations their followers have about leaders (Rosing et al, 2022). Since our work demonstrates that people prefer to give power to those who exhibit self-control, further understanding of how leader self-control influences followers and team performance is especially important.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence obtained from higher education in the United Arab Emirates highlighted that high levels of met expectations resulted in better job satisfaction and organizational commitment as well as an increase in organizational trust [56]. Rosing et al's [57] empirical investigation carried out among firefighters in Germany revealed that met follower expectations acted as a partial mediator between leader trait selfcontrol and follower trust in the leader. Recent research carried out in Bosnia and Herzegovina revealed that employees' fulfillment of expectations about their job enhanced overall job satisfaction [58].…”
Section: Met Expectationsmentioning
confidence: 99%